ANALISIS MENGUKUR TINGKAT KEPENTINGAN DAN KEPUASAN NASABAH PT. BANK MANDIRI CABANG PALANGKA RAYA - Lite Lite (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
There are quite similar reasons for debtors in selecting bank to the reasons inkeeping funds. It is not merely concerning interest rate and facilities, service is also animportant factor. This factor is greatly important regarding business activity between onebank and others can be said to be the same. The different thing is a matter of services.This research is located in Mandiri Bank Palangka Raya Branch. This researchaims to (1) determine and analyze the level of conformity of interest level of serviceelements according to customers on the performance that has been conducted by MandiriBank Palangka Raya Branch (2) to determine customers’ satisfaction on the services thathave been given so that it can assist the Mandiri Bank performance to achieve betterquality improvement through determination of main priority.The samples are 100 customers of Mandiri Bank Palangka Raya Branch as therespondents using accidental sampling technique, the analysis used is customers’Importance-Performance analysis. This analysis uses Cartesians Diagram divided intofour quadrants. In this research, there are some main considerations by Mandiri BankPalangka Raya Branch namely (a) Teller attention to the customers, employeewillingness to service the customers (b) Waiting time in the queue (c) existence ofMandiri ATM machine (d) Interest rate level given by the bank.